MORE THAN JUST ENGAGING? TIKTOK AS AN EFFECTIVE EDUCATIONAL TOOL. - Hasnah Am Abdul Aziz; Siti Zaiton Mohd Dali, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
TikTok, a video-sharing social media platform, has rapidly become one of the most popular social networking sites in recent years, with over 1 billion monthly active users. With its easy-to-use interface, short-form videos, and viral content, TikTok provides an innovative way for educators to engage and educate students. This paper aims to investigate the usefulness of TikTok as an effective educational tool by creating a fun and interactive learning environment. TikTok is an ideal platform for effective and engaging learning for several reasons such as allows students to be creative and use their imagination to create unique, meaningful content for variety of subjects such as science, math, social studies, and language arts. Several studies have shown that TikTok can be a valuable learning tool, improving students' engagement, motivation, and overall learning experience. Despite its popularity, Tiktok use in education also raises concerns and challenges that need to be addressed by the scholars. This study was conducted using a purposeful sampling of KPTMAS students, with data collected through an online survey administered via Google Form. The findings revealed that high acceptance and usefulness of TikTok as an educational tool among KPTMAS students. In conclusion, TikTok has proven to be an effective and efficient platform for learning. Its unique features provide an innovative way for educators to engage students and teach valuable skills. As social media platforms continue to influence the way people consume information, TikTok could be an important tool for educators to create a more engaging and effective learning experience.